Tablet-based kitchen/cashier system - Sim, Eng Keat. (2011)
The high daily transactions in a good restaurant necessitate a Kitchen/Cashier System. The system not only tracks the sales but can simplify communications between the kitchen and the waiter. Wireless orders to the Kitchen/Cashier System can be forwarded to the kitchen printer for fulfilment of orders. The system will also help to solve various operational and record keeping problems.